International Theatre Olympics The Artistic and Intercultural Power of Olympism - Kim, Jae Kyoung; SpringerLink (Online service) (Singapore : Springer Singapore(Imprint), 2016)
This pivot examines how the Theatre Olympics, born in 1995, have served to enrich each host country's culture, community, and foreign relations. Looking at the host country's political, social, and cultural circumstances, it considers how the festival expands the notion of Olympism beyond its application to the Olympic Games, expressing the spirit of Olympism and interculturalism in each country's distinct cultural language. It emphasizes the festival's development over the twenty years of its existence and how each festival's staging has reflected the national identity, theatre tradition, and cultural interest of the hosting country, as well as how each festival director's artistic principle has attempted to accomplish cultural exchange through their productions. Jae Kyoung Kim, completed her PhD in Theatre studies at the University of Georgia, USA and is currently a teaching professor at Chung-Ang University, Republic of Korea. Her research is primarily focused on international theatre festivals, intercultural theatre, and East-Asian theatre.
Introduction -- Tragedy Shall Last Forever -- The East and the Nature -- Theatre, Carnival, and the People -- A Step Closer to Greece -- Humanism and Globalization -- Glory of Beijing Olympics -- Conclusion.
Keywords: Theatre and Performance Studies; Sociology of Culture